Види Iridaceae Juss. у заплаві Десни - Лукаш, О.В.; Рак, О.О.; Подорожний, Д.С. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
Выявлены новые местонахождения 5 видов семейства Iridaceae в пойме Десны в пределах Восточного Полесья, проанализированы их распространение и ценотическая приуроченность. Редкие виды (Iris sibirica L., Gladiolus imbricatus L., G. tenuis M. Bieb.) исследованы на популяционном уровне. Выявлены два новых места натурализации Sisyrinchium septentrionale Bicknell. на территории Украины. The new sites are revealed, the distribution and cenotic attachment of 5 species of family Iridaceae in flood-lands of the Desna river within the limits of East Polissa are analysed. The rare species (Iris sibirica L., Gladiolus imbricatus L., G. tenuis M. Bieb.) on a population level are investigated. Two new places of naturalization of Sisyrinchium septentrionale Bicknell. in territory of Ukraine are revealed.